2013
DOI: 10.1093/nar/gkt071
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive approach to zinc-finger recombinase customization enables genomic targeting in human cells

Abstract: Zinc-finger recombinases (ZFRs) represent a potentially powerful class of tools for targeted genetic engineering. These chimeric enzymes are composed of an activated catalytic domain derived from the resolvase/invertase family of serine recombinases and a custom-designed zinc-finger DNA-binding domain. The use of ZFRs, however, has been restricted by sequence requirements imposed by the recombinase catalytic domain. Here, we combine substrate specificity analysis and directed evolution to develop a diverse col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(91 citation statements)
references
References 45 publications
3
88
0
Order By: Relevance
“…Site-specific recombinase (and potentially transposase) enzymes present fewer problems by tightly controlling generation of double-strand breaks to coordinate donor-target coupling. By fusing the catalytic domain of a small serine recombinase 44 to Cas9, analogous to previous zinc finger and TAL fusions 45 , it may be possible to create an RNA-guided recombinase enzyme. Because the activity of such retargeted fusion recombinases is generally low, extensive directed evolution may be necessary to produce a useful RNA-guided recombinase.…”
Section: Expanding Cas9 Functionalitymentioning
confidence: 99%
“…Site-specific recombinase (and potentially transposase) enzymes present fewer problems by tightly controlling generation of double-strand breaks to coordinate donor-target coupling. By fusing the catalytic domain of a small serine recombinase 44 to Cas9, analogous to previous zinc finger and TAL fusions 45 , it may be possible to create an RNA-guided recombinase enzyme. Because the activity of such retargeted fusion recombinases is generally low, extensive directed evolution may be necessary to produce a useful RNA-guided recombinase.…”
Section: Expanding Cas9 Functionalitymentioning
confidence: 99%
“…First and foremost are the development of new tools capable of introducing genomic modifications in the absence of DNA breaks. Targeted recombinases (Akopian et al 2003;Mercer et al 2012), which can be programmed to recognize specific DNA sequences (Gaj et al 2013;Sirk et al 2014;Wallen et al 2015) and even integrate therapeutic factors into the human genome (Gaj et al 2014b), are one such option. More recent work has indicated that single-base editing without DNA breaks can be achieved using an engineered Cas9 nickase complex (Komor et al 2016), although it remains unknown how effective this technology is in therapeutically relevant settings.…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that off-target effects exist, and resolving them will be important for future clinical applications of this technology. As research continues to optimize current protocols, more creative approaches such as the use of recombinant fusion proteins provide new opportunities (75,76,189 …”
Section: Future Directions Of Genome Editing Technologymentioning
confidence: 99%